Experimental design of beam under flexural loading / Mohd Fadzrul Ahmad, Mohamad Azlan Mohamed Aris and Hasnadi Jamaain - Ahmad, Mohd Fadzrul; Mohamed Aris, Mohamad Azlan; Jamaain, Hasnadi (2001)
Beam is a device that is used in many constructions in the world. For our final project, we design how to measure a stress and deflection of beam. In our test to find the stress, we use Wheatstone Bridge Circuit. This circuit will be discussed in chapter 4. We must know how to design this “experimental Design of Beam under Flexural loading." with rigidly and can measure the beam without any failure. So, we should know the procedure before we can start our project. It is important to know the procedure for design to ensure that our project is success.